Effect of plasmonic nanoshell-based nanofluid on efficiency of direct solar thermal collector. (25th March 2018) - Duan, Huiling; Tang, Liangliang; Zheng, Yuan; Xu, Chang
Highlights: The plasmonic effect is introduced in solar thermal area to enhance light absorption. The irradiance within the nanofluid attenuates rapidly at resonant wavelength. The use of nanoshell-based nanofluid can significantly reduce the concentration. The volume fraction of SiO2 /Au nanofluid needed is only 1/5 of Au nanofluid. Abstract: The plasmonic effect is introduced in solar thermal area to enhance light absorption. The solar irradiance within the nanofluid attenuates rapidly at wavelength of 560 nm, contributed from the localized surface plasmon resonance (LSPR) excited on the SiO2 /Au nanoshells. A one-dimensional transient energy equation coupled with radiative transport equation is solved to analyze the photothermal efficiency of SiO2 /Au nanofluid. The use of plasmonic nanoshell-based nanofluid can significantly reduce the concentration of nanofluid used in direct solar thermal collector. For an equal temperature rise, the volume fraction of SiO2 /Au nanoshell-based nanofluid is only 1/5 of Au nanofluid. This is a great advantage of employing plasmonic nanoshell-based nanofluid for solar thermal absorption. The photothermal efficiency increases with nanofluid height and tends to an asymptotic value due to the exponentially attenuation of spectral solar irradiance with incident depth. For the plasmonic nanofluid based on SiO2 /Au nanoshells considered in this study, the proper height would be 10 mm. Further increasing the height, the photothermal efficiency varies a little.